Immigration Policy and the Skills of Immigrants to Australia, Canada, and the United States - Heather Antecol; Deborah A. Cobb-Clark; Stephen J. Trejo (Institute for the Study of Labor (IZA), 2001)
Census data for 1990/91 indicate that Australian and Canadian immigrants have higher levels of English fluency, education, and income (relative to natives) than do U.S. immigrants. This skill deficit for U.S. immigrants arises primarily because the United States receives a much larger share of immigrants from Latin America than do the other two countries. After excluding Latin American immigrants, the observable skills of immigrants are similar in the three countries. These patterns suggest that the comparatively low overall skill level of U.S. immigrants may have more to do with geographic and historical ties to Mexico than with the fact that skill-based admissions are less important in the United States than in Australia and Canada.
Keywords: J31; J68; J61; 330; Immigration; immigrant skills; immigration policy; Einwanderung; Humankapital; Qualifikation; Einwanderungsrecht; Vergleich; Australien; Kanada; USA